Dysphagia postfundoplication: More commonly hiatal outflow resistance than poor esophageal body motility - Wilshire, Candice L.; Niebisch, Stefan; Watson, Thomas J.; Litle, Virginia R.; Peyre, Christian G.; Jones, Carolyn E.; Peters, Jeffrey H. (Surgery, 2012)
Historically, risk assessment for postfundoplication dysphagia has been focused on esophageal body motility, which has proven to be an unreliable prediction tool. Our aim was to determine factors responsible for persistent postoperative dysphagia. Fourteen postfundoplication patients with primary dysphagia were selected for focused study. Twenty-five asymptomatic post-Nissen patients and 17 unoperated subjects served as controls. Pre- and postoperative clinical and high-resolution manometry parameters were compared. Thirteen of the 14 symptomatic patients (92.9%) had normal postoperative esophageal body function, determined manometrically. In contrast, 13 of 14 (92.9%) had evidence of esophageal outflow obstruction, 9 of 14 (64.3%) manometrically, and 4 of 14 (28.6%) on endoscopy/esophagram. Median gastroesophageal junction integrated relaxation pressure was significantly greater (16.2 mm Hg) in symptomatic than in asymptomatic post-Nissen patients (11.1 mm Hg, P = .05) or unoperated subjects (10.6 mm Hg, P = .02). Sixty-four percent (9/14) of symptomatic patients had an increased mean relaxation pressure. Dysphagia was present in 9 of 14 (64.3%) preoperatively, and elevated postoperative relaxation pressure was independently associated with dysphagia. These data suggest that postoperative alterations in hiatal functional anatomy are the primary factors responsible for post-Nissen dysphagia. Impaired relaxation of the neo-high pressure zone, recognizable as an abnormal relaxation pressure, best discriminates patients with dysphagia from those without symptoms postfundoplication.